Modernization of higher education and science financing system in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
The education system is an essential component of the socio-economic system of the state, whichhas an impact on all aspects of its activities. The influence of education on economic growth is proved byleading Russian, domestic and foreign economists. The implemented reform in the sphere of higher educationis aimed at the simultaneous solution of a number of problems: first of all, to improve the qualityof education and training of personnel, integration into the international educational space, structurallysubstantialacademic design is adequate to the needs of society, the state, employers, the individual.Higher education and the science system are subject to radical changes in the world closely related tothe implementation of the idea of a knowledge-based economy. Funding plays a very important rolehere, in fact its function and effect. The level of expenditures and the way of their distribution is todayabout the potential of a given country. In the most developed economies, the financing of higher educationand science is closely related to the efficiency, needs of the enterprise sector and is a derivativeof healthy competition. This article is devoted to the problems of financing the education and sciencesystems in Kazakhstan in conditions of the formation of a knowledge-based economy. The main stagesof budgetary and extra-budgetary financing of educational institutions are considered. Studied modelsof normative financing of education, features, problems and consequences of their implementation. Thearticle is intended for specialists in the field of economics, management and financing of the educationand science system.